Unique microRNA expression profiles in plasmic exosomes from intrahepatic cholestasis of pregnancy - Yao Kong; Yongchi Zhan; Daijuan Chen; Xixi Deng; Xinghui Liu; Tingting Xu; Xiaodong Wang (BMC, 2023)
Abstract Background Intrahepatic cholestasis of pregnancy (ICP) is strongly associated with an increased risk of adverse perinatal outcomes. Total bile acid (TBA) levels in the late second or third trimester are a major factor in the diagnosis. Here, we sought to establish the miRNA expression profile of plasm exosomes of ICP and identify possible biomarkers for the diagnosis of ICP. Methods This case-control study involved 14 ICP patients as the experimental group and 14 healthy pregnant women as the control group. Electron microscopy was used to observe the presence of exosomes in plasma. Nanosight and Western blotting of CD63 was used to assess exosome quality. Among them, three ICP patients and three controls were used for isolation plasmic exosome and preliminary miRNA array analysis. The Agilent miRNA array was utilized to dynamically monitor the miRNA expression in plasmic exosomes of included patients in the first trimester(T1), second trimester (T2), third trimester (T3), and delivery (T4). Then, Quantitative real-time Polymerase chain reaction was used to identify and validate differentially expressed miRNAs in plasma-derived exosomes. Results The expression levels of hsa-miR-940, hsa-miR-636, and hsa-miR-767-3p in plasma-derived exosomes of ICP patients were significantly higher than those of healthy pregnant women. Besides, these three miRNAs were also significantly up-regulated at the plasma, placental, and cellular levels (P < 0.05). The diagnostic accuracy of hsa-miR-940, hsa-miR-636, and hsa-miR-767-3p was further evaluated by the ROC curve, the area under the curve (AUC) values for each were 0.7591, 0.7727, and 0.8955, respectively. Conclusions We identified three differentially expressed miRNAs in the plasma exosomes of ICP patients. Hence, hsa-miR-940, hsa-miR-636, and hsa-miR-767-3p may be potential biomarkers for enhancing the diagnosis and prognosis of ICP.